European Survey Study Among Plastic/Breast Surgeons on the Use of and Opinion Toward Autologous Fat Transfer: With Emphasis on Breast Surgery - Groen, Jan-Willem (Surg Innov, 2018)
Objective. The aim of this study is to examine the experience of European surgeons on autologous fat transfer (AFT) and highlight differences between countries and levels of experience. Background Data. The popularity of AFT causes an increase in sophisticated scientific research and clinical implementation. While results from the former are well-documented, important aspects of the latter are far less recognized. Methods. An international survey study about surgeon background, besides AFT familiarity, technique, and opinion, was distributed among surgeons from 10 European countries. The differences between countries and levels of experience were analyzed using a logistic regression model. Results. The mean respondent age, out of the 358 completed questionnaires, was 46 years. Ninety-seven percent of the respondents were plastic surgeons, who practiced AFT mostly in breast surgery and considered themselves experienced with the technique. The thigh and abdomen were less favored harvest locations by the Belgium and French respondents, respectively, and both the French and Austrian respondents preferred manual aspiration over liposuction in harvesting the fat. Despite minor differences between countries and experience, the intraglandular space was injected in all subgroups. Conclusions. The expanding use of AFT in Europe will lead to more experience and heterogeneity regarding the technique. However, despite an obvious adherence to Coleman’s method, deviations thereof become more apparent. An important example of such a deviation is the ongoing practice of intraglandular AFT despite being a contraindication in various European guidelines. These unsafe practices should be avoided until scientific clarification regarding oncological safety is obtained and should therefore be the focus of surgeon education in Europe.